Determinants of Eco-Budgeting and Control in Medical Waste Management: A Behavioral Approach - Eka Ardhani Sisdyani; Ida Bagus Gede Fajar Manuaba; I Gusti Agung Gede Utara Hartawan; I Wayan Pradnyantha Wirasedana; Anak Agung Vidyaswari Kedisan; Ni Komang Ayu Devi (Universitas Pendidikan Ganesha, 2024)
This study explores the determinants influencing the intention to adopt eco-budgeting and eco-controlling mechanisms in medical waste management. While existing research primarily addresses the technical aspects, there has been scant focus on the behavioral factors that influence hospital management's adoption of these environmentally conscious practices. Employing an associative quantitative methodology, this research gathered data from 125 managers across 15 private general hospitals in Denpasar City and Badung Regency, utilizing surveys and analyzing the results with partial least squares (PLS). The findings indicate that environmental concerns and stakeholder pressure significantly impact managers' intentions to implement eco-budgeting. To effectively translate these intentions into tangible practices, managers are found to deploy four types of eco-control mechanisms: belief, boundary, diagnostic, and interactive controls. These insights offer critical guidance for hospital administrators and policymakers, underscoring the importance of behavior-driven strategies in enhancing medical waste management. The study emphasizes the necessity of integrating behavioral factors into environmental management frameworks to foster the development of eco-efficient and environmentally sustainable practices within hospitals, ultimately contributing to the broader goal of green hospital initiatives.